Conservative Management of Small Bowel Enterocutaneous Fistulas: Possibilities and Limitations - Milina, Srđan; Nikolić, Marija; Trifunovic, Nemanja; Surla, Dimitrije; Dević, Ana; Trifunović, Jovana (Medical Gazzette, 2026)
Introduction: Enterocutaneous fistulas (ECF) are complex and potentially life-threatening complications characterized by a pathological communication between the gastrointestinal tract and the skin. They most commonly arise as a consequence of abdominal surgical procedures, while spontaneous occurrence is rarer and seen in patients with inflammatory bowel diseases, malignancies, or after radiation therapy. Spontaneous closure is possible but uncommon, depending on a number of clinical and local factors.This paper aims to present the current principles, possibilities, and limitations of conservative treatment of small bowel enterocutaneous fistulas, with a focus on factors influencing their spontaneous closure.Methodology: This is a narrative literature review. The search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library for articles published between 2010 and 2025. Keywords used were: enterocutaneous fistula, conservative management, spontaneous closure, intestinal fistula. Studies in English and Serbian addressing conservative approaches to treating small bowel fistulas were included. Factors influencing the course and outcome of treatment were analyzed.Main findings: Key factors influencing spontaneous closure of ECF include low output (
Keywords: enterocutaneous fistula, conservative treatment, small bowel, nutritional support, spontaneous closure